TV Lokal Pembentuk Identitas Kultural Antara Harapan Dan Kenyataan (Studi Kasus Terang Abadi Televisi Surakarta) - Satriana Didiek Isnanta (Institut Seni Indonesia Surakarta, 2008)
The endorsement of Undang Undang /UU 2002 number 32 (Indonesian Law System) about broadcase is to emerge an important standing point of the existence of local television. It is because of the fulfillness of the formal legal and democratic in Indonesia. Local television implementating spirit of autonomous is felt by the viewer as the spectrum of our broadcast. Covering by dense local programs local television has always served the best programs for Indonesian viewers realizing the local genious.Besides, the ideal of this UU broadcast is to build the foundation for the system of broadcast decentralisation. In short, the local government has also right to take a better benefits from its broadcast both the range of the diversity of the content and diversity of ownershipIt looks very ideal when the UU 2002 about broadcast want to make a good and fair share of economical benefits. But we have a big question : How far our local investor can compete with nasional even gobal investors? How can local program compete with others from national or even global program?. Moreover, can local program format as a local culture identity can compete againts national or even global program format?Those are three big questions that really want to be analysed in this paper. Using the focus in case study of Terang Abadi Television (TATV Surakarta) as local televisionIt is expected to find out an ideal television format program to make a ultural identity as well as profit for economical sides. Key words : Local television, cultural identity.